2019
DOI: 10.1590/1414-431x20198565
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of ultrasonography synovitis with disease activity and clinical response to etanercept treatment in juvenile idiopathic arthritis patients

Abstract: This study aimed to investigate the correlation of ultrasonography (US) of synovitis with disease activity and clinical response to etanercept (ETN) in juvenile idiopathic arthritis (JIA) patients. Eighty-two JIA patients who underwent ETN treatment for 24 weeks were consecutively enrolled. US evaluations of 28 joints (shoulder, elbow, wrist, metacarpophalangeal, and proximal interphalangeal of hands and knee) at baseline were performed using grey-scale US and power doppler (PD) US, and US synovitis was define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Besides, the combinations of other disease-related drugs (such as methotrexate (MTX), leflunomide (LEF) and other disease-modifying antirheumatic drugs (DMARDs)) were allowed, and the related information was documented. After 24 weeks of ETN treatment, the clinical response was assessed referring to the American College of Rheumatology (ACR) Pediatric (pedi) 50 criteria: 50% improvement from baseline in at least 3 of any 6 measures of the JIA core sets without more than 1 measure worsening by over 30% (Consolaro et al 2009;Zhou and Gu 2019). The 6 measures were erythrocyte sedimentation rate (ESR), joints with active arthritis, joints with limited range of motion, physician's global assessment of disease activity, parent/patient global assessment of overall well-being and CHAQ scores.…”
Section: Treatment and Assessmentmentioning
confidence: 99%
“…Besides, the combinations of other disease-related drugs (such as methotrexate (MTX), leflunomide (LEF) and other disease-modifying antirheumatic drugs (DMARDs)) were allowed, and the related information was documented. After 24 weeks of ETN treatment, the clinical response was assessed referring to the American College of Rheumatology (ACR) Pediatric (pedi) 50 criteria: 50% improvement from baseline in at least 3 of any 6 measures of the JIA core sets without more than 1 measure worsening by over 30% (Consolaro et al 2009;Zhou and Gu 2019). The 6 measures were erythrocyte sedimentation rate (ESR), joints with active arthritis, joints with limited range of motion, physician's global assessment of disease activity, parent/patient global assessment of overall well-being and CHAQ scores.…”
Section: Treatment and Assessmentmentioning
confidence: 99%
“…Furthermore, Zhou and Gu, 2019 (55) showed that the number of joints showing synovitis at baseline was positively correlated with CRP, ESR, number of joints with active disease.…”
Section: Discussionmentioning
confidence: 98%
“…Another prospective study reported that the number of ultrasound positive joints (out of 28) decreased significantly after 24 weeks treatment with etanercept. The same study concluded that a higher number of ultrasound positive joints at baseline was seen in patients who achieved ACRPedi50 response compared to patients who did not, and that it was an independent predictive factor of response (odds ratio – OR = 1.438, 95% CI: 1.091–1.897) ( Zhou and Gu, 2019 ). On the other hand, there are conflicting results as to whether positive ultrasound findings in JIA patients with inactive disease can predict flares, although it should be noted that a minority of patients were on biologic treatment in these studies ( Magni-Manzoni et al, 2013 ; Miotto et al, 2017 ; De Lucia et al, 2018 ; Zhao et al, 2018 ).…”
Section: Imaging Biomarkers Of Response To Biologic Treatmentsmentioning
confidence: 99%